Não sei viver sem meu celular : os celulares redefinindo dinâmicas e papeis sociais das novas crianças - Silva, Aparecida Oneide de Almeida (2015)
This paper, from the perspective of Anthropology of Consumption and material culture, considering the context of consumption and the centrality of communication and its materiality in urban universe, aims to analyze the expression and circulation practices or cultural content associated with the cell phone in everyday life children in their social circle. It is an ethnography that accompanied the daily eleven children between nine and twelve, at most, for a period of thirteen months, in two cities in the northwestern region of Paraná, belonging to the middle class and families with similar socio-cultural profiles. Through this study, is expected to highlight the richness and complexity of the material and symbolic dimensions involved in the daily processes, ie how consumption practices related to mobiles phones, these kids not only affect family relations, but also in the circle social to which they belong. And as such communication processes are giving visibility to the social construction of their autonomy.